Repeated recall on source misattribution in Alzheimer's disease. Issue 10 (26th November 2021) - El Haj, Mohamad; Robin, Frédérique
ABSTRACT: We assessed the effect of repeated recall on item memory and source monitoring in Alzheimer's disease (AD). AD patients and controls were instructed to either look at or imagine items. They then had to either retrieve the items without indicating their source in three consecutive free recall tests, or to remember the source of the retrieved items in three consecutive source tests. Results showed a significant increase in item memory across all three free recall tests and all three source monitoring tests in control participants, but not in AD patients. More source misattributions were observed in AD patients and controls in the third source test than in the first and second tests. The absence of beneficial effect of repeated recall on item memory in AD patients may be attributed to compromise in memory consolidation processes, while the increase in source misattributions due to repetitions may be attributed to the inflation effect.